Correlation between peak expiratory flow rate and pectoralis muscle length - Subramanian, Visalakshi H.; Chennakeshawaran, Aruna; Kumar, Vijay Krishna (International Journal of Research in Medical Sciences, 2020)
Background: Peak expiratory flow rate (PEFR) is a measure of the maximum speed of exhalation after a deep inspiration. The peak expiratory flow is measured by a device named peak flow meter. This study concentrates on the correlation of the PEFR with the pectoral muscle length. Methods: It is a cross sectional study of 30 convenient samples based on gender distribution where the PEFR and pectoralis muscle length were measured in the subjects. Results: Statistical analysis shows that there is a significant correlation between right pectoralis major general muscle length and PEFR (p=0.030), left pectoralis major general muscle length and PEFR (p=0.014), right pectoralis major clavicular end muscle length with PEFR (p=0.010). Conclusions: There is a significant correlation between peak expiratory flow and pectoralis muscle length.